Doing philosophy in the Philippines : the Thomasian collection - Co, Alfredo P., editor (Manila : UST Publishing House, 2023)
"Filipino philosophy has become a buzzword in the history and development of philosophical scholarship in the country. For over half a century, the question of the existence of Filipino philosophy has preoccupied older and newer generations of Filipino scholars. Various methods have been espoused to promote the idea of an indigenous Filipino philosophy, but a good number of have also been levelled against it. This multivolume collection is a continuation of attempts to substantially contribute to this lively discourse."
Includes bibliography.
English.
Keywords: Philosophy--Filipino